Pemanfaatan Energi Listrik Portabel untuk Penerangan dan Aerator Kolam - Nur Hudha Wijaya; Rinasa Agistya Anugrah; Wisnu Kartika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The potential of Wirokerten Village, Banguntapan District, Bantul Regency, Yogyakarta Special Region is quite a lot. The potentials were tourist villages, herbal medicines, BUMDes (fishing, paving block factory construction, hydroponics, and waste sorting). Currently, Wirokerten village had four hectares of land for fisheries which BUMDes manage. However, some things were a problem for the fish breeder group: the absence of water filters for pools so that the water was free from harmful bacteria, water that lack oxygen in each pool, so it could not be used for fish breeding, and lack of lighting at the location of the pool, because the lighting was taken from residents' homes by pulling long cables while the distance from residential areas was quite far. The solution to these problems requires supporting technology to realize the expectations of fish farmer groups, namely portable aerators and pool lighting and water filters to sterilize waste in pool water reservoirs. The purpose of this community service was to help fish farming groups to be able to do fish breeding and rearing independently with the help of aerators and portable lighting and to be able to filter water in pool water reservoirs before it flows into each pool plot.